(untitled) (Journal of Applied Learning and Teaching, 2023)
Generation Zs (hereafter Gen Zs) are the new generation of adults entering the workforce and becoming key stakeholders and leaders in the new century. Relatedly, this is also the generation posited to reorient the paradigm in business, leadership, and governance back towards stronger sustainable development agendas. Consequently, exploring the sustainability orientations and educational outcomes of the evolving Gen Z cohort is beneficial. Whilst there has been significant extant discourse on various research dimensions concerning the preceding generations (e.g., Gen Y/Millennials, Gen X and Boomers), research on the Gen Zs is at a nascent stage. Specifically, there has been no known study to date exploring the collective thematic dimensions of (1) ecopedagogy and sustainability education, (2) Gen Z generational characteristics and perceptions, and (3) governmental and institutional policy implications in higher education. This paper is conceptual in nature and aims to critically review the literature characterising Gen Zs and advance the conceptual and contextual understanding of this generational cohort within the above thematic dimensions. An ecopedagogical conceptual framework is also developed and proposed for further empirical research.